Pegylated Interferon Treatment for the Effective Clearance of Hepatitis B Surface Antigen in Inactive HBsAg Carriers: A Meta-Analysis - Song, Aixin; Lin, Xiao; Lu, Junfeng; Ren, Shan; Cao, Zhenhuan; Zheng, Sujun; Hu, Zhongjie; Li, Hong; Shen, Chengli; Chen, Xinyue (Frontiers in Immunology, 2021)
Abstract Background: Expanding antiviral therapy to benefit more populations and optimizing treatment to improve prognosis are two main purposes in current guidelines on antiviral therapy. However, the guidelines do not recommend antiviral therapy for inactive hepatitis B surface antigen (HBsAg) carriers (IHCs). Recent studies showed that antiviral therapy was effective with good treatment outcomes in IHC populations. We conducted a systematic review and meta-analysis of HBsAg clearance and conversion in IHCs. Methods: We searched PubMed, Embase, Medline, and Web of Science to retrieve articles on HBsAg clearance in IHCs published between January 2000 and August 2021. Data were collected and analyzed using the random effects model of meta-analysis. Results: A total of 1029 IHCs from 11 studies were included in this analysis. The overall HBsAg clearance rate was 47% (95% confidence interval (CI): 31% - 64%) with a conversion rate of 26% (95% CI: 15% - 38%) after 48 weeks of Pegylated interferon (Peg-IFN) treatment. In the control group (including nucleos(t)ide analog (NA) treatment or no treatment), the overall HBsAg clearance rate was only 1.54% (95% CI: 0.56% - 3.00%), which was much lower than that in the Peg-IFN group. Further analysis showed that a low baseline HBsAg level and long treatment duration contributed to a higher HBsAg clearance rate. Conclusion: This study showed that IHCs could be treated or even clinical cured. After Peg-IFN treatment, the HBsAg clearance rate was 47%, and the conversion rate was 26%, which were much higher than the findings of previous studies on Peg-IFN treatment in patients with chronic hepatitis B (CHB). A low baseline HBsAg level and long treatment duration were associated with HBsAg clearance in IHCs. Therefore, antiviral therapy is applicable for IHCs, a population that may be clinically cured.